Presence of indigenous culture in the artistic scene: transculturation and hybrid culture in Latin America - Torquatro, Jaqueline (Revista do Colóquio, 2024)
This article talks about the transculturation process that took place in Latin America, following the arrival of Europeans. To develop this research, we analyzed examples of public art installed in Espírito Santo, focusing on highlighting the symbolic references presented by such pieces. Through this research, we concluded that the way in which original peoples were represented in works of public art was profoundly impacted by the insertion of European culture in colonial Brazil.